Neural circuits for valence updating in social memory - Narutoshi Suto; Mu-Yun Wang; Shota Morikawa; Myung Chung; Kentaro Tao; Ziyan Huang; Yuji Ikegaya; Haruki Takeuchi; Shinichiro Kira; Teruhiro Okuyama (Science, 2026)
Social animals recognize familiar conspecifics and selectively avoid harmful ones. As social relationships shift, continuous updating of social valence is essential, yet the underlying neural mechanisms remain unclear. Here, by artificially transforming a previously neutral conspecific into an aggressive one, we show that valence updating depends on enhanced synaptic connectivity and physiological changes within the hippocampal ventral CA1 (vCA1)–basolateral amygdala (BLA)–nucleus accumbens (NAc) circuit. Following defeat, social memory engram neurons in the vCA1 strengthened their connections with BLA neurons carrying negative valence. The vCA1–BLA–NAc neural circuit flexibly regulates adaptive social behaviors.